HUMAN PHENOTYPIC MORALITY AND THE BIOLOGICAL BASIS FOR KNOWING GOOD: with Pat Bennett and John A. Teske, "The Road Is Made by Walking: An Introduction"; J. Wentzel van Huyssteen, "Can We Still Talk about 'Truth' and 'Progress' in Interdisciplinary Thinking Today?"; Jonathan Marks, "What If the Human Mind Evolved for Nonrational Thought? An Anthropological Perspective"; Phillip Cary, "Right‐Wing Postmodernism and the Rationality of Traditions"; Margaret Boone Rappaport and Christopher Corbally, "Human Phenotypic Morality and the Biological Basis for Knowing Good"; Christian Early, "Philosophical Anthropology, Ethics, and Love: Toward a New Religion and Science Dialogue"; Warren S. Brown, "Knowing Ourselves as Embodied, Embedded, and Relationally Extended"; and John A. Teske, "Knowing Ourselves by Telling Stories to Ourselves.". Issue 3 (18th August 2017) - Rappaport, Margaret Boone; Corbally, Christopher
Abstract: Co‐creating knowledge takes a new approach to human phenotypic morality as a biologically based, human lineage specific (HLS) trait. Authors from very different backgrounds (anthropology and biology, on the one hand, and astronomy, philosophy, and theology, on the other) first review research on the nature and origins of morality using the social brain network, and studies of individuals who cannot "know good" or think morally because of brain dysfunction. They find these models helpful but insufficient, and turn to paleoanthropology, cognitive science, and neuroscience to understand human moral capacity and its origins long ago, in the genus Homo . An unusual narrative capturing "morality in action" takes the reader back 900, 000 years, and then the authors analyze the essential features of moral thinking and behavior as expressed by early and later species on our lineage. In what has primarily been the province of philosophers to date, the authors' morality model is presented for further scientific testing.